Nanotechnology-based drug delivery systems for control of microbial biofilms: A review - Dos Santos Ramos, Matheus Aparecido [UNESP]; Da Silva, Patrícia Bento [UNESP]; Spósito, Larissa [UNESP]; De Toledo, Luciani Gaspar [UNESP]; Bonifácio, Bruna vidal [UNESP]; Rodero, Camila Fernanda [UNESP]; Dos Santos, Karen Cristina [UNESP]; Chorilli, Marlus [UNESP]; Bauab, Taís Maria [UNESP] (Taylor & Francis, 2018)
Since the dawn of civilization, it has been understood that pathogenic microorganisms cause infectious conditions in humans, which at times, may prove fatal. Among the different virulent properties of microorganisms is their ability to form biofilms, which has been directly related to the development of chronic infections with increased disease severity. A problem in the elimination of such complex structures (biofilms) is resistance to the drugs that are currently used in clinical practice, and therefore, it becomes imperative to search for new compounds that have anti-biofilm activity. In this context, nanotechnology provides secure platforms for targeted delivery of drugs to treat numerous microbial infections that are caused by biofilms. Among the many applications of such nanotechnology-based drug delivery systems is their ability to enhance the bioactive potential of therapeutic agents. The present study reports the use of important nanoparticles, such as liposomes, microemulsions, cyclodextrins, solid lipid nanoparticles, polymeric nanoparticles, and metallic nanoparticles, in controlling microbial biofilms by targeted drug delivery. Such utilization of these nanosystems has led to a better understanding of their applications and their role in combating biofilms.
Keywords: Anti-biofilm activity; Microbial biofilms; Nanotechnology systems